2017
DOI: 10.1212/wnl.0000000000004028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hyperacute infarct volume using ASPECTS and brain CT perfusion core volume

Abstract: Objective:To compare the accuracy of Alberta Stroke Program Early Computed Tomography Score (ASPECTS) and CT perfusion to detect established infarction in acute anterior circulation stroke.Methods:We performed an observational study in 59 acute anterior circulation ischemic stroke patients who underwent brain noncontrast CT, CT perfusion, and MRI within 100 minutes from CT imaging. ASPECTS scores were calculated by 4 blinded vascular neurologists. The accuracy of ASPECTS and CT perfusion core volume to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 21 publications
(30 reference statements)
5
62
0
1
Order By: Relevance
“…However, contrary to this hypothesis, our results indicate that CTP CV does not alter the overall performance of the prognostic model. Consistent with our findings, a recent study also found no significant difference between predictive accuracies of CTP and CT ASPECTS in predicting hyperacute MRI lesion volumes in acute ischemic stroke 19. Therefore, our results suggest that additional incorporation of perfusion imaging data in preintervention prognostic models such as the THRIVE, PRE, or MR PREDICTS scores will not yield higher prognostic accuracy 6 9…”
Section: Discussionsupporting
confidence: 90%
“…However, contrary to this hypothesis, our results indicate that CTP CV does not alter the overall performance of the prognostic model. Consistent with our findings, a recent study also found no significant difference between predictive accuracies of CTP and CT ASPECTS in predicting hyperacute MRI lesion volumes in acute ischemic stroke 19. Therefore, our results suggest that additional incorporation of perfusion imaging data in preintervention prognostic models such as the THRIVE, PRE, or MR PREDICTS scores will not yield higher prognostic accuracy 6 9…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that most patients who finally presented GIC had the high ASPECTS on admission despite presumed large infarct cores on CTP, suggesting that in this early time window, patient selection according to noncontrast CT might avoid wrong exclusions from EVT [24].…”
Section: Discussionmentioning
confidence: 75%
“…ASPECTS = Alberta Stroke Program Early CT Scale; n = number of patients; OR = odds ratio; CI = confidence interval; ICH = intracerebral hemorrhage; mRS = modified Rankin Scale; NIHSS = National Institutes of Health Stroke Scale; and TICI = thrombolysis in cerebral infarction, with a score of 2b/3 indicating >50% recanalization of the previously occluded vessel. on noncontrast CT in the hyperacute (<3 hours) 10 and acute (<6 hours) 11 settings. However, the relationship between early noncontrast CT changes and perfusion core volumes has not been well characterized in the extended window (6 to 24 hours after LKN).…”
Section: Discussionmentioning
confidence: 99%